BALINESE GAMELAN LEARNING PROCESS DURING THE COVID-19 PANDEMIC: Proses Pembelajaran Gamelan Bali di Masa Pandemi Covid-19 - I Nengah Rata Artana; I Made Dwi Wira Ardana; Ni Luh Christine Prawitha Sari Suyasa (SOSIOEDUKASI, 2022)
This research aims to find out the learning process of online Balinese Gamelan during the Pandemic Covid-19. Learning Balinese Gamelan online during the Covid-19 pandemic is a Balinese gamelam learning solution for foreigner where it can be conducted by adapting the digital era especially for artist who are able to adapt. To maintain the continuity of the art activities in the area of 4.0, innovation in Balinese gamelan is a must. Methods of online interviews and online observation at karawitan art studio and Dwara-Dwani in the Gianyar area are used in this research. The discussion on Balinese gamelan learning during the Covid-19 Pandemic will be discussed through the analysis of the process of Balinese gamelan learning activities carried out by a Balinese artist or a composer, Ida Bagus Made Widnyana, resulted that practice of Balinese gamelan during the Covid-19 pandemic did not face any obstacles because the artists are able to adapt to the development of information technology